VARIABILITY OF ANKLE MOVEMENTS AS A FATIGUE FACTOR IN RUNNERS - Negodenko, E.S.; Medvedeva, E.V.; Kapilevich, L.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to assess the stability of the ankle trajectory in runners of various qualifications under conditions of fatigue. Methods and structure of the study. During the study, two groups were formed: a group of highly qualified runners - 8 people (4 men and 4 women) with more than 5 years of trail running experience, age 30±3 years, average preferred running speed 13±1.33 km/h; without injuries for the past and current calendar year. Control group - novice runners - 10 people (7 men and 3 women) with half a year experience of smooth running on asphalt/hard ground, age 18±2 years, speed in the mixed pulse zone 7±2.2 km/h. The movement registration method was used to study the instability of the ankle trajectory in runners of various qualifications under conditions of fatigue. Results and conclusions. It is shown that fatigue that develops during long-term running loads (45 minutes) is accompanied by an increase in the variability of ankle movements, and if this increase is not so significant for experienced athletes, then for beginner runners it is very significant and can serve as a risk factor for sports injuries. This aspect must be taken into account when planning the training process, when choosing sports shoes and when assessing the risk of injury.